Familial Spinal Neurofibromatosis - Pascual-Castroviejo, I.; Pascual-Pascual, S.-I.; Velazquez-Fragua, R.; Botella, P.; Viazo, J. (Neuropediatrics, 2007)
Familial spinal neurofibromatosis (FSNF) is a rare localized subtype of NF1 which shows neurological symptomatology during adult life. Only a few families have been reported to date. We describe a family in which three members in two generations, mother, son and daughter, were affected. The patients, aged 48, 22 and 18 years, had spinal bilateral neurofibromas affecting all spinal roots. Spinal symptoms were not present in any of the patients. However, the son had generalized nerve sheath tumors that caused important signs of peripheral neuropathy. The daughter also had benign tumors that involved the left optic nerve and chiasm and the left cerebellar hemisphere. The spinal neurofibromas underwent an important growth in size between 20 and 22 years of age. A specific mutation G848R, 2542 G > C in NF1 exon 16 was present in all three patients.
Keywords: Neurofibromatosis type I (NF1); familial spinal neurofibromatosis (FSNF); spinal neurofibroma; peripheral nerve neurofibroma